Peran Mahasiswi Mengoptimalisasi Intervensi Sosial Mikro dalam Mengatasi Pengucilan pada Anak di Panti Asuhan Al-Marhamah - Putri, Ivana Dwi; Ritonga, Fajar Utama (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This journal presents a case study regarding the micro-social intervention practices undertaken by Ivana a USU FISIP Social Welfare student in handling a case of exclusion experienced by V, a 4-year-old girl in foster care. V became a victim of exclusion as a result of his reactive nature towards the treatment of his peers, who were later deemed “stupid” by the nursing home environment. The intervention focused on providing individualized support to V, education of the nursing home environment to foster empathy and acceptance, as well as strengthening the caregiver role. Micro-intervention methods that included the stages of engagement, assessment, planning, intervention, implementation, evaluation, and termination were applied. Companion results showed there were positive changes on V, such as increased confidence and acceptance of the care environment, as well as increased caregiver persistence. This case study reflects that children with foster care backgrounds have great potential that is highly dependent on how the environment shapes them, and that social welfare science can be a tool of real change on the ground.